Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.cmet.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinases Maintain Protein Homeostasis and Survival of Cancer Cells upon Glutathione Depletion

Abstract: Highlights d Most cancer cell lines are largely insensitive to GSH depletion d Deubiquitinases (DUBs) protect cancer cells upon inhibition of GSH synthesis d Inhibition of DUBs and GSH synthesis causes ER and proteotoxic stress and cell death d Combined targeting of DUBs and GSH blocks tumor growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 110 publications
(111 reference statements)
4
114
1
1
Order By: Relevance
“…Figure 8D) did not induce lipid ROS ( Figure 3E) and had no impact on cell viability ( Figure 3F). This result highlights contradictory findings regarding the sufficiency of glutathione depletion for the induction of ferroptosis in different cell lines (13,30). We inferred that in PDA cells, the loss of one or more additional cysteine-derived metabolites may be critical to the induction of ferroptosis.…”
mentioning
confidence: 80%
“…Figure 8D) did not induce lipid ROS ( Figure 3E) and had no impact on cell viability ( Figure 3F). This result highlights contradictory findings regarding the sufficiency of glutathione depletion for the induction of ferroptosis in different cell lines (13,30). We inferred that in PDA cells, the loss of one or more additional cysteine-derived metabolites may be critical to the induction of ferroptosis.…”
mentioning
confidence: 80%
“…Recent studies have suggested that a majority of cancer cell lines survive upon 72 hours of BSO treatment despite potent inhibition of GSH levels at this time point. Moreover, these studies have demonstrated that chronic BSO treatment, up to 9 days, is required in induce cell death or stasis 27 . In our models, 6 hours of BSO treatment was sufficient to diminish GSH levels (Figure S3E) , in line with previous kinetic data 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these studies have demonstrated that chronic BSO treatment, up to 9 days, is required in induce cell death or stasis 27 . In our models, 6 hours of BSO treatment was sufficient to diminish GSH levels (Figure S3E) , in line with previous kinetic data 27 . By contrast, co-treatment of GOT1 knockdown with BSO was cytotoxic at 72 hours, while BSO alone was cytostatic (Figures 3D and S3F) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These redox Western samples were mixed with a 4× nonreducing buffer before separation by SDS-PAGE. For analyses of TXN1 oxidation, a previously established, urea-PAGE protocol was followed (Du et al, 2013; Harris et al, 2019). Two control lysates were fully reduced with dithiothreitol (VWR) and then treated with iodoacetic acid (Sigma-Aldrich) or iodoacetamide (Sigma-Aldrich) to represent fully oxidized or reduced TXN protein.…”
Section: Methodsmentioning
confidence: 99%